Influence of earthquake ground-motion duration on damage estimation - application to steel moment resisting frames - Barbosa, Andre R.; Ribeiro, Filipe L. A.; Neves, Luís A. C. (Wiley, 2016)
This paper presents an analytical study evaluating the influence of ground motion duration on structural damage of 3-story, 9-story, and 20-story SAC steel moment resisting frame buildings designed for downtown Seattle, WA, USA, using pre-Northridge codes. Two-dimensional nonlinear finite element models of the buildings are used to estimate the damage induced by the ground motions. A set of 44 ground motions is used to study the combined effect of spectral acceleration and ground motion significant duration on drift and damage measures. In addition, 10 spectrally equivalent short-duration shallow crustal ground motions and long-duration subduction zone records are selected to isolate duration effect and assess its effect on the response. For each ground motion pair, incremental dynamic analyses are performed at at least 20 intensity levels and response measures such as peak interstory drift ratio and energy dissipated are tracked. These response measures are combined into two damage metrics that account for the ductility and energy dissipation. Results indicate that the duration of the ground motion influences, above all, the combined damage measures, although some effect on drift-based response measures is also observed for larger levels of drift. These results indicate that because the current assessment methodologies do not capture the effects of ground motion duration, both performance-based and code-based assessment methodologies should be revised to consider damage measures that are sensitive to duration.